Regulierung und Wettbewerb im Bereich der Netzinfrastrukturen: Begründung, Regeln und Institutionen - Frank Bickenbach (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
This paper starts by analyzing the consequences that technical and economic charactcristics of network industries have for the relationship between competition and regulation in these industries. A discussion of alternative regulatory rules shows that normative regulatory economics does not provide results specific and robust enough to serve as concrete rules for regulatory policy. Thus, questions of the appropriate institutions of regulatory policy and the vertical (federal) and horizontal allocation of regulatory competencies come to the fore. However, there are no simple answers to these questions either. The paper suggests, that a ,,transaction cost politics" approach might help to base the analysis of regulatory institutions on a more solid theoretical basis than traditional normative or public choice approaches (economic theories of federalism, interest group theories etc.) are able to provide.
Keywords: D72; D82; H11; L43; L51; 330; Netzzugang; Regulierung; Marktversagen; Institutionalismus; Vertragstheorie; Agency Theory; Transaktionskosten; Theorie